Characterising variability in youth mental health service populations: A detailed and scalable approach using digital technology. (June 2023) - Capon, William; Hickie, Ian B; McKenna, Sarah; Varidel, Mathew; Richards, Matthew; LaMonica, Haley M; Rock, Daniel; Scott, Elizabeth M; Iorfino, Frank
Objective: This study utilised digital technology to assess the clinical needs of young people presenting for care at headspace centres across Australia. Method: 1490 young people (12–25 years) who presented to one of 11 headspace services from four geographical locations (urban New South Wales, urban South Australia, regional New South Wales, and regional Queensland) completed a digital multidimensional assessment at initial presentation. Characteristics were compared between services and geographical locations. Results: We identified major variation in the demographics, and the type and severity of needs across different services. Individuals from regional services were more likely to be younger, of Aboriginal and Torres Strait Islander origin, and present with psychotic-like symptoms and suicidality, while those in urban areas were more likely to have previously sought help and have problematic alcohol use. Further differences in age, distress, depressive symptoms, psychotic-like experiences, trauma, family history, alcohol use, education/employment engagement, and days out of role were identified between different urban sites. Conclusions: The variability between services provides insight into the heterogeneity of youth mental health populations which has implications for appropriate early intervention and prevention service provisions. We propose that integrating digital technologies has the potential to provide insights for smarter service planning and evaluation.